2006
DOI: 10.1002/cne.21020
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial mitochondria-rich cells and associated innervation in adult and developing zebrafish

Abstract: Studies of ion regulation by mitochondria-rich cells (MRCs) of transport epithelia in fish have revealed many processes by which ion homeostasis is achieved. However, the control of these mechanisms and, particularly, the extent of nervous system involvement are not completely understood. We characterized the potential innervation of MRCs in various gill and extrabranchial tissues involved in ion transport in the model vertebrate the zebrafish. Confocal and conventional microscopy of whole-mount preparations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 73 publications
(146 reference statements)
1
32
1
Order By: Relevance
“…These cells are characterized by apical localization of the enzyme Na + /K + -ATPase and an extensive cytoplasmic tubular network ( Fig. 6B; Laurent and Dunel-Erb, 1984;Quinn et al, 2003;Jonz and Nurse, 2006). Early studies investigating the function of the pseudobranch suggested that it may act as a gland, a sensory organ involved in O 2 chemoreception, or take part in osmoregulation (Laurent and Rouzeau, 1972;Laurent and Dunel-Erb, 1984).…”
Section: The Pseudobranchmentioning
confidence: 99%
See 1 more Smart Citation
“…These cells are characterized by apical localization of the enzyme Na + /K + -ATPase and an extensive cytoplasmic tubular network ( Fig. 6B; Laurent and Dunel-Erb, 1984;Quinn et al, 2003;Jonz and Nurse, 2006). Early studies investigating the function of the pseudobranch suggested that it may act as a gland, a sensory organ involved in O 2 chemoreception, or take part in osmoregulation (Laurent and Rouzeau, 1972;Laurent and Dunel-Erb, 1984).…”
Section: The Pseudobranchmentioning
confidence: 99%
“…There is evidence that the teleost pseudobranch receives afferent innervation (Laurent and Rouzeau, 1972;Laurent and Dunel-Erb, 1984), but similar nerve fibres in zebrafish are immunopositive for the synaptic vesicle protein SV2 (Jonz and Nurse, 2003), suggesting a neurosecretory or efferent role of these fibres. Moreover, since innervation of PBCs occurs apically, rather than basolaterally (Laurent and Dunel-Erb, 1984;Jonz and Nurse, 2006), the physiological significance of these cells would appear to be limited to internally oriented functions that may take place between the basolateral membrane and the vasculature, such as hormone secretion or chemical sensing of the blood. While the precise function of the pseudobranch and its component cells is currently speculative, further study of the nature of PBC innervation may reveal significant clues about the role of this potentially important organ in fish.…”
Section: The Pseudobranchmentioning
confidence: 99%
“…Studies by Jonz and Nurse (2003) on zebrafish (Danio rerio) gill innervation showed that the origin of innervation is extrinsic (cell body of nerve fiber is extrinsic to the gill) as well as intrinsic (cell body of nerve fiber is intrinsic to the gill). The same authors also demonstrated that branchial ICs are extrinsically innervated 7 .…”
Section: Introductionmentioning
confidence: 84%
“…The gills, and presumably the branchial ICs, are innervated by the IX and X cranial nerves 7,[23][24][25] . These nerves carry both efferent and afferent inputs to and from the gill, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation